Smart TV business regulation and collaboration among business operators and regulators: Focus on the case analysis of Smart TV blocking and IPTV regulation process in Korea - Yaeeun Kim; Younghoon Chang; Myeong-cheol Park (International Telecommunications Society (ITS), 2012)
The lack of detailed guideline of network traffic management has led complex conflicts among ICT players. Among them, the most severe case was KT and Samsung's case: Korea Telecom (KT) once blocked Internet connection of Samsung Smart TV service users. This aroused the needs of a reasonable policy establishment. On the process of making policy regarding network management, participants, for example network operators, device and platform providers, and contents providers, are sticking to their own stances. Their passive responses are now leading deepen problems. Thus, we focused on the way of conflict management in a policy level. With internal and external case studies and conflict management grid, we substantiated that the dispute participants will be better off altogether under a reasonable regulation and collaboration.
Keywords: 330; Smart TV Service; Conflict Management; Regulation; Collaboration.